Motherhood and Childhood during Apartheid: A Study of Four Texts - Roya , Witness; Ngcobo, Sandiso (Journal of Ecohumanism, 2025)
Black women played numerous roles during apartheid. They were mothers, grandmothers, sisters, aunts, political activists, to mention a few. There is scant research and literary works on experiences of ordinary people during apartheid though that is changing. This paper seeks to contribute towards this growing discourse by contradicting stereotypical depictions of black women as victims, trouble causers, among others, through foregrounding their dynamism. Shirley, Goodness and Mercy, Native Nostalgia, Born a Crime and Other Stories, hereafter, “Born a Crime” and Song for Sarah: Lessons from my mother, hereafter, “Song for Sarah” were purposively sampled. Findings indicated that women’s adoption of explicit and implicit forms resistance enabled them to take apartheid in their stride and at times means of apartheid unintentionally benefitted black people. This was revealed through the four texts’ use of techniques such as humour and multiple narratives. This paper adds to growing corpus of studies on experiences of marginalized groups during apartheid. It is hoped that the paper will: stimulate further studies on women and children’s experiences of apartheid, encourage authors, researchers and the general populace to embrace diversity as depicted in the texts.